Distribution and diagnostics of dog dirofilariasis in the city of Poltava - Kruchynenko, O. (Scientific Progress & Innovations, 2022)
The article presents data on a common nematodosic disease in dogs (Canis lupus familiaris Linnaeus, 1758) caused by pathogens Dirofilaria spp., which are of interest to doctors of humane and veterinary medicine. Dirofilariasis is a dangerous transmissible, zoonotic disease caused by helminths belonging to the roundworm class Nematoda, order Spirurida, family Filariidae, genus Dirofilaria. Pathogens of the disease are extremely common in many countries of the world and are adapted to exist in different climatic zones, which is facilitated by the complex biology of parasite development. The aim of the study was to determine the epizootological features of dirofilariasic infestation in dogs in the city of Poltava and to establish which dye solution (gentian violet, brilliant green, methylene blue or Lugol's) is the most effective for staining microdirofilaries. To achieve the goal, hemolarvoscopic studies were carried out according to the method of I. S. Dakhno (2004) on 138 dogs of different age groups and sexes during the year. Laboratory studies were performed on the basis of the Scientific Laboratory of the Department of Parasitology and Veterinary- Sanitary Examination of the Poltava State Agrarian University. Risk factors were assessed using the Chisquare test (Pearson's test of agreement). The results of our research established that the parasitism of Dirofilaria spp. in dogs in the city of Poltava, the average is 29.7 %, and the intensity of invasion is 148.3 microdirofilariae in 1 cm3 of blood. According to the results obtained regarding the age-related dynamics of dirofilariasis in dogs, it was noted that EI increased with age. The highest rates were in dogs 3–6 years old – 41.0 %. In the seasonal aspect, the highest extent of dirofilariasic infestation was in summer (June) and amounted to 39.0 %, and the intensity of invasion, respectively, in autumn in September – 193.2 microdirofilaries in 1 cm3 of blood. According to the research results, males get sick more often than females (P<0.05). The use of 0.1 % dye solutions: gentian violet, brilliant green and methylene blue for the diagnosis of heartworm disease contributes to the staining of microdirofilaries and ensures their effective detection in the blood of dogs.